The Problem of Food Wasting in Poland and Shaping the Pattern of Sustainable Consumption - Niedek, Mikołaj; Krajewski, Karol (Studia Ecologiae et Bioethicae, 2021)
The aim of the article is to outline the directions of appropriate activities related to the development of sustainable consumption. The background are the results of research and analysis on the level of food losses and wastage in the food chain, carried out as part of the PROM research project. The starting point of the article is to outline the issue of food losses and wastage in the light of the data available at the global, European and national levels, and to show that this issue is interdisciplinary ‒ social, economic, and environmental, and that it is a proper subject of ecophilosophical and ecoethical reflection. The trends, which are negative for the environment, society and economy, related to the contemporary level of food losses and wastage at all stages of the agri-food chain, require changes in the current consumption patterns to comply with the requirements of sustainable development. This transformation requires the changes in axiological and ethical patterns, which are especially recommended at the final stage of the food chain - the purchase of food by consumers and the way of dealing with it in households. The article also outlines the directions of further research aimed at preparing an appropriate, comprehensive theoretical basis for designing adequate implementation activities for sustainable development of consumption.